A small-scale solar organic Rankine cycle combined heat and power system with integrated thermal energy storage. (25th December 2017) - Freeman, J.; Guarracino, I.; Kalogirou, S.A.; Markides, C.N.
Highlights: Thermal energy storage solutions for a domestic-scale solar CHP system are compared. The system includes a 15-m 2 solar collector array and an ORC engine. Diurnal and seasonal performance in the climates of Cyprus and the UK are assessed. Phase change materials are compared to conventional thermal energy storage options. Hydrated-salt PCMs show the highest electrical work output per unit storage volume. Abstract: In this paper, we examine integrated thermal energy storage (TES) solutions for a domestic-scale solar combined heat and power (S-CHP) system based on an organic Rankine cycle (ORC) engine and low-cost non-concentrating solar-thermal collectors. TES is a critical element and distinct advantage of solar-thermal systems. It can allow, depending on how it is implemented, improved matching to the end-user demands, improved load factors, higher average efficiencies and overall performance, as well as reduced component and system sizes and costs, especially in climates with high solar-irradiance variability. The operating temperature range of the TES solution must be compatible with the solar-collector array and with the ORC engine operation in order to maximise the overall performance of the system. Various combinations of phase change materials (PCMs) and solar collectors are compared and the S-CHP system's performance is simulated for selected months in the contrasting climates of Cyprus and the UK. The most important performance indicator of the ORC engine, i.e., net-power output, and the required TES volume are compared and discussed. The PCM-TES solutions that enable the best summer performance from an ORC engine sized for a nominal ∼1-kWe output in combination with a 15-m 2 solar collector array result in diurnal volume requirements as low as ∼100 L in Cyprus and 400–500 L in the UK. However, the required TES volume is strongly influenced by the choice of operational strategy for the system in matching the domestic load profiles. In a full-storage strategy in which electrical energy generation from the ORC engine is offset to match the week-day evening peak in demand, it is found that a ∼20% higher total daily electrical output per unit storage volume can be achieved with a PCM compared to water as a sensible storage medium. The isothermal operation of the PCMs during phase-change allows for smaller diurnal storage temperature swings and higher energy conversion efficiencies from the solar collector array. These results are useful in informing the development of small-scale solar-thermal heat and power systems and of suitable integrated TES solutions for such applications.